Redox conditions on the Anadarko Shelf of Oklahoma during the deposition of the "Mississippian Limestone". (June 2020) - Adeboye, O.O.; Riedinger, N.; Wu, T.; Grammer, G.M.; Quan, T.M.
Abstract: A multiproxy approach, including stable nitrogen isotopes and redox sensitive trace elements, was employed in order to evaluate the impact of depositional redox conditions on organic matter accumulations within the Mississippian Limestone interval in the Anadarko Shelf of Oklahoma and also to investigate hydrocarbon source rock potential of the Mississippian Limestone in the study area. Nitrogen isotopes (δ 15 N), total organic carbon (TOC), and concentrations of redox-sensitive trace elements (Cu, Mn, Mo, Ni, U, V) were measured on samples from a core drilled in Canadian County, Oklahoma. Values of TOC are between 0 and 2.5 wt. % and average 0.8 wt. % in the studied interval of the core. The δ 15 N data (3‰–14‰, average 8 ± 1‰) indicate sediment deposition under oxic to suboxic water conditions. This interpretation of depositional redox conditions is supported by elemental redox proxies which show no enrichment relative to average carbonate. Our geochemical data suggest that the Mississippian Limestone is unlikely to be an oil source rock due to pervasively oxic to suboxic depositional redox conditions which would have resulted in oxidation of organic matter. Highlights: Water column and benthic redox conditions at time of deposition were oxic-suboxic. Depositional redox does not influence organic matter accumulation in study site. Mississippian Limestone sediments have poor oil source rock potential due to oxygenated conditions during deposition.